2013
DOI: 10.1038/tp.2013.61
|View full text |Cite
|
Sign up to set email alerts
|

Mixed emotions: the contribution of alexithymia to the emotional symptoms of autism

Abstract: It is widely accepted that autism is associated with disordered emotion processing and, in particular, with deficits of emotional reciprocity such as impaired emotion recognition and reduced empathy. However, a close examination of the literature reveals wide heterogeneity within the autistic population with respect to emotional competence. Here we argue that, where observed, emotional impairments are due to alexithymia—a condition that frequently co-occurs with autism—rather than a feature of autism per se. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

42
396
4
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(445 citation statements)
references
References 112 publications
42
396
4
3
Order By: Relevance
“…Emotion recognition difficulties are also found in individuals with ASD (Uljarevic and Hamilton 2013), although there is a high rate of variability in performance Jones et al 2011). Bird and Cook (2013) have suggested that the presence of alexithymia may account for this variability, and found that alexithymia, not autism severity, predicts difficulties in identifying emotions from facial or vocal expressions Heaton et al 2012), as well as with the strength of neural responses to watching people in pain (Bird et al 2010). The explanatory role of cooccurring alexithymia in ASD is proposed to be specific to particular facets of social cognition, namely emotion processing.…”
Section: Alexithymia and Social Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotion recognition difficulties are also found in individuals with ASD (Uljarevic and Hamilton 2013), although there is a high rate of variability in performance Jones et al 2011). Bird and Cook (2013) have suggested that the presence of alexithymia may account for this variability, and found that alexithymia, not autism severity, predicts difficulties in identifying emotions from facial or vocal expressions Heaton et al 2012), as well as with the strength of neural responses to watching people in pain (Bird et al 2010). The explanatory role of cooccurring alexithymia in ASD is proposed to be specific to particular facets of social cognition, namely emotion processing.…”
Section: Alexithymia and Social Cognitionmentioning
confidence: 99%
“…Bird and Cook (2013) have suggested that emotion recognition and empathy atypicalities seen in individuals with ASD may result from (co-occurring) alexithymia rather than ASD itself. Furthermore, given that alexithymia is associated with higher rates of anxiety and depression (Bankier et al 2001;Berthoz et al 1999;Honkalampi et al 2000) and atypical responses to sensory input (Herbert et al 2011;Kano et al 2007;Katz et al 2009;Lyvers et al 2014;Nyklicek and Vingerhoets 2000) in non-ASD populations, individual differences in alexithymia may also be associated with the increased rates of internalising disorders and sensory sensitivities in ASD.…”
mentioning
confidence: 99%
“…In the clinical domain, a growing appreciation of the heterogeneity present in socio-cognitive disorders (e.g. [13]) has led to an increased emphasis on understanding the mechanisms underlying deficits in specific socio-cognitive abilities, rather than considering clinical groups as presenting with homogeneous patterns of impairment [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It is supported by a complimentary foreword written by Professor A.D. (Bud) Craig who is the world's foremost expert on interoception. Like Craig, I was impressed with Mahler's grasp of contemporary research, some of which has been conducted by my group leader and his collaborators (see Bird and Cook 2013). The book contains many hypotheses that are currently under investigation, reinforcing hopes that our research holds translational value.…”
mentioning
confidence: 99%
“…Alexithymia is characterized by difficulties in recognizing emotions from internal bodily sensations. The author correctly notes that alexithymia frequently co-occurs with ASD (approximately 55 %; see Bird and Cook 2013) and lists alexithymia questionnaires under measures by which to assess interoception (Chapter 3). Unfortunately, however, Mahler does not recognize that ASD and alexithymia are independent constructs: Alexithymia is not required for a diagnosis of ASD nor it is present in all individuals with autism.…”
mentioning
confidence: 99%